The association between dysregulated adipocytokines in early pregnancy and development of gestational diabetes. Issue 8 (15th September 2017) - Abell, Sally K.; Shorakae, Soulmaz; Harrison, Cheryce L.; Hiam, Danielle; Moreno‐Asso, Alba; Stepto, Nigel K.; De Courten, Barbora; Teede, Helena J.
Abstract: Background: To investigate the association of adipocytokines and other inflammatory markers with development of GDM. Methods: Serum adipocytokines and inflammatory markers were studied at 12 to 15 weeks gestation using biobanked control samples from a randomised trial. Study participants were identified as high risk for GDM using a validated clinical risk prediction tool. Markers were tested using commercial ELISA kits for high molecular weight (HMW) adiponectin, interleukin‐6 (IL‐6), plasminogen activator inhibitor‐1, visfatin, omentin‐1, sex‐hormone binding globulin, monocyte chemoattractant protein, and asymmetrical dimethylarginine. The association between each biomarker and development of GDM at 24 to 28 weeks was evaluated using multivariable logistic regression analysis adjusted for maternal factors. Results: There were no differences in age, parity, country of birth, smoking, body mass index, or family history of diabetes in women with normal glucose tolerance ( n = 78) and women who developed GDM ( n = 25). Women with GDM were more likely to have a past history of GDM ( P = 0.004). HMW adiponectin (odds ratio OR 0.37 [95% confidence interval 0.19–0.74]), omentin‐1 (0.97 [0.94–0.99]), and IL‐6 (1.87[1.03–3.37]) were associated with development of GDM, after adjustment for maternal age, body mass index, and past history of GDM. The other markers were not associated with GDM development. Conclusions: Decreased high molecular weight adiponectin and omentin‐1 and increased IL‐6 may enhance sensitivity of early risk prediction tools for women at high risk of GDM. This may allow early identification and opportunities for prevention of GDM and adverse outcomes. Further research is required in large validation studies to confirm these results.